A história do fonema /s/ do Tupi antigo (The history of the phoneme /s/ in Ancient Tupi) - Costa, Consuelo de Paiva Godinho (2013)
The most common differences between languages branch Tupi and Guarani branch relate to changing penultimate stress words in the Tupi Guarani oxítonas words in the languages and the correspondence between the phoneme /s/ Branch Tupi and the phoneme /h/ Branch Guarani. In this work, we deal with the second difference through a diachronic study of phonological process that gave generate currently Tupi languages that have the phoneme /s/ and Guarani languages that have, in addition to / h / expected, also /s/ "frozen "in certain terms, relating the (s) alleged (s) protofonema (s) with the unfolding found in Old Tupi and Guarani Old, firstly, and, secondly, in Nhandewa-Guarani, Guarani currently a variety spoken in São Paulo and northern Paraná.KEYWORDS: Phonology. Tupi. Guarani. prophonemes